2019
DOI: 10.4103/aian.aian_221_18
|View full text |Cite
|
Sign up to set email alerts
|

Conglomerate ring-enhancing lesions are common in solitary neurocysticercosis and do not always suggest neurotuberculosis

Abstract: Background and Purpose:Differentiating between neurocysticercosis (NCC) and neurotuberculosis has serious therapeutic implications and this distinction relies heavily on neuroimaging. Few case reports discuss the conglomeration of ring-enhancing lesions (RELs) in patients with solitary NCC. The aim of our study is to describe the imaging findings of conglomerate RELs in a cohort of patients with solitary NCC, emphasizing the frequency of conglomeration.Materials and Methods:This retrospective study included 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…21 Garg et al, in a similar study of NCC cases, reported 96% of the lesion distribution to be supratentorial, 3% to be brainstem, and 1% to be cerebellar. 24 Observations from these studies including ours show that tuberculomas tend to have a higher prevalence of infratentorial distribution than NCCs.…”
Section: Discussionmentioning
confidence: 52%
“…21 Garg et al, in a similar study of NCC cases, reported 96% of the lesion distribution to be supratentorial, 3% to be brainstem, and 1% to be cerebellar. 24 Observations from these studies including ours show that tuberculomas tend to have a higher prevalence of infratentorial distribution than NCCs.…”
Section: Discussionmentioning
confidence: 52%
“…Previously considered unusual, Garg et al recently highlighted such phenotype in more than half of their cases on CT scans. [10][11][12]15 Epidemiologically, tuberculosis is also prevalent in NCC endemic populations. Tuberculomas also present similarly on imaging with only a minority of cases having other supporting features outside CNS.…”
Section: Discussionmentioning
confidence: 99%
“…We frequently encounter such atypical phenotype in solitary NCC and other centers have similar experience. [10][11][12] Apart from tuberculosis, such morphology also needs exclusion of other possibilities like non-tubercular infections, demyelination and more importantly tumors. [10][11][12][13][14][15] This may cause delay in starting or disruption of ongoing cysticidal treatment, initiation of anti-tubercular treatment (ATT) or even lead to brain biopsy to rule out a neoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which unusual in NCC. [ 4 ] Conglomerate NCC are common presentation of single NCC lesion[ 5 ] and these may become more than 2.5 cm in size, mimicking giant NCC lesions, which is a rare form of NCC. [ 6 ] Most giant NCC lesions are cysts located in cisterns and may be associated with perilesional edema in adjacent brain parenchyma.…”
mentioning
confidence: 99%